The Implementation of Student-Centered Learning - Gusmira, Yenti (International Journal of Educational Sciences and Development, 2025)
This qualitative descriptive study explores the implementation of Student-Centered Learning (SCL) at MTsN 1 and MTsN 2 Bukittinggi through interviews, observations, and documentation. At MTsN 1, active learning strategies such as discussions, project-based learning (PBL), and differentiated instruction are being applied, particularly in classes using the Independent Curriculum and Semester Credit System (SKS). Teachers act more as facilitators, and students show increased engagement and independence. Meanwhile, MTsN 2 shows a slower shift toward SCL, with teacher-centered approaches still dominant and low student participation. Limited digital learning use, weak reflective practices, and inadequate teacher training hinder effective SCL implementation. NVivo 12 was used to analyze and visualize emerging themes and patterns. The study suggests that to enhance SCL, schools need to strengthen teacher competence, improve learning infrastructure, and build a culture of reflection to support inclusive, student-focused education. These findings offer valuable insights for policymakers and educators aiming to improve 21st-century learning environments in Islamic secondary schools